Research Progress on Relation Between BTBP1 and Tumor Progression and Treatment - XIN Tong; SUN Yue; HU Jing (Zhongliu Fangzhi Yanjiu, 2022)
PTBP1, a widely-studied RNA binding protein, regulates mRNA splicing, translation, stability and localization. PTBP1 participates in a variety of ncRNA acting processes, affects tumorigenesis and tumor progression. In terms of tumor therapy, PTBP1 may act as a key factor to affect the target of targeted drugs and influence tumor resistance. This article reviews the role of PTBP1 in tumor and its research progress in tumor treatment.